Pengaruh Rasa Aman terhadap Moral Pajak Warga Negara Indonesia - Tarizah, Dhiya Alfiyah; Erina, Lili; Syahrudin, Ade; Imania, Katriza (Universitas Batanghari Jambi, 2025)
The aim of this research is to examine how the tax morale of the Indonesian population is influenced by a sense of security. This research uses quantitative methodology. The secondary data used is secondary data from the results of the 7th World Value Survey (WVS) site survey. A total of 3,200 residents aged the same or more than 18 years were the research sample. The research findings show that residents' tax morality is positively and significantly influenced by their sense of security. Education level is one of the sociodemographic elements that positively and significantly influences tax morality; Educated people will definitely have higher tax morality.